THE EFFECT OF STRESS COMPLAINTS ON SLEEP QUALITY AMONG MEDICAL STUDENTS CLASS OF 2019 OF MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Andi Hendra Yusa, Andi Hendra Yusa; Irawan Ade Triadi, (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
Sleep is a significant physiological process in the life of living things including humans. Reduced sleep duration or quality of sleep in today's society is closely related to lifestyle, increased consumption of technology, increased workload, and social needs. The purpose of this study was to identify the effect of stress complaints on sleep quality in students of the Faculty of Medicine, University of Muhammadiyah Makassar. The research method is observational analytic with a cross-sectional design and random sampling technique. There were 55 students who experienced stress and who experienced poor sleep quality, from the results of the chi square test obtained a value of p = 0.001 (p <0.05), then statistically Ha was accepted which stated that there was an effect of stress complaints on sleep quality in students of the Faculty of Medicine Muhammadiyah Makassar University.